Protein partners of the eEF1Bβ subunit of the translation elongation complex eEF1B in the nuclear fraction of human lung carcinoma cells - Kapustian, L.M.; Dadlez, M.; Negrutskii, B.S. (Вiopolymers and Cell, 2017)
Aim. To identify novel protein partners of translation factor eEF1Bβ in nucleus of human lung carcinoma cells. Methods. Protein partners of eEF1Bβ in the nuclear fraction of A549 cells were identified by co-immunoprecipitation (co-IP) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS). Specific protein partners of eEF1Bβ were further selected by using the results of previously published global, quantitative and dynamic mapping of protein subcellu-lar localization with help of “Mapofthecell” program. Results. 104 high-scored proteins interact-ing with eEF1Bβ in the nuclear fraction of A549 cells have been identified by mass-spectrometry. Among these proteins, 9 partners of eEF1Bβ were confirmed by the co-fractionation approach. Functional analysis of the partners has divided them on the pro-oncogenic (lung-cancer related) and neutral/anti-oncogenic moieties. These two groups are estimated to be spatially separated in human cancer cells. Conclusions. The position of eEF1Bβ as a link between the oncogenic and neutral/tumor-suppressor moieties of its protein partners in nucleus of lung cancer cells is sug-gested. Deciphering of a possible role of the eEF1Bβ distribution between the pro-cancer or anti-cancer communities of its protein partners can be a subject of further research. Мета. Виявити нових білків-партнерів фактора трансляції eEF1Bβ в ядрі клітин карциноми легені. Методи. Білки-партнери eEF1Bβ, отримані з ядерного екстракту клітин А549 методом ко-імунопреципітації (co-IP), були ідентифіковані за допомогою высокоефективної рідинної хроматографії з тандемною мас-спектрометрією (LC-MS/MS). Подальше підтвердження білків-партнерів проводили із використанням опублікованих даних глобального, кількісного і динамічного картування субклітинної локалізації білків за допомогою програми Mapofthecell. Результати. 104 білки, які взаємодіють із eEF1Bβ в ядерній фракції клітин карциноми легені A549 були ідентифіковані мас-спектрометрією. Проміж цих білків, 9 партнерів eEF1Bβ були підтверджені даними із прецизійного субклітинного фракціонування. За допомогою функціонального аналізу ці білки-партнери можуть бути поділені на про-онкогенну і нейтральну/анти-онкогенну групи. Передбачено, що ці групи можуть бути просторово розділені в ракових клітинах людини. Висновки. Запропоновано, що eEF1Bβ може бути проміжною ланкою між онкогенною і нейтральною/пухлиносупресорною групами партнерів цього білка в ядрі ракових клітин. Розшифрування можливої ролі залучення eEF1Bβ до про-ракової або анти-раковими спільнот білкових партнерів цього білку може бути предметом подальших дослiджень. Цель. Выявление новых белков-партнеров фактора трансляции eEF1Bβ в ядре клеток карциномы легкого. Методы. Белки-партнёры eEF1Bβ, полученные из ядерного экстракта клеток А549 методом ко-иммунопреципитации (co-IP), были идентифицированы с помощью высокоэффективной жидкостной хроматографии с тандемной масс-спектрометрией (LC-MS/MS). Дальнейшее подтверждение белков-партнеров проводили с использованием опубликованных ранее данных глобального, количественного и динамичного картирования субклеточной локализации белков с помощью программы «Mapofthecell». Результаты. Методом масс-спектрометрии было идентифицировано 104 белка, взаимодействующих с eEF1Bβ в ядре клеток A549. Из этих белков, 9 партнеров eEF1Bβ были подтверждены данными, полученными при подробном субклеточном фракционировании. С помощью функционального анализа эти белки-партнеры можно разделить на про-онкогенную і нейтральную/анти-онкогенную группы. Предсказано, что эти группы могут быть разделены в пространстве в раковых клетках человека. Выводы. Выдвинуто предположение, что eEF1Bβ может быть промежуточным звеном между онкогенной и нейтральной/опухоле-супрессорной группами его партнеров в ядре раковых клеток. Расшифровка возможной роли вовлечения eEF1Bβ в про-раковую или анти-раковую группы его белковых партнеров может быть предметом дальнейших исследований.